Hubungan antara Self Control dengan Problematic Smartphone Use pada Mahasiswa Wanita - Anggraeini, Fara Della Regita Ayu; Purnomo, Jusuf Tjahjo (Universitas Muhammadiyah Metro, 2024)
Problematic smartphone use is a condition where individuals cannot control their smartphone usage and feel uncomfortable if they are not using smartphones, so it gives rise to negative effects on its users. One of the factors that affects problematic smartphone use is self-control. This study aims to find out the relationship between self-control the problematic smartphone uses in female students. The method used in this study is quantitative with a correlational design. As many as 154 participants involved in this study are using incidental sampling. The instrument used in this study is the Problematic Mobile Phone Use Scale (PMPUS) (α = 0.904) and the self-control scale (α = 0.837). The result showed that there is negative relationship between self-control and problematic smartphone use in female students with r = -0.546 and α = 0.000 (p<0.05).